Stimulating knowledge sharing and informal learning : The influence of social networking tools and techniques - Albert , Geeta; Ibrahim, Nor Takrim (Persatuan Pustakawan Malaysia, 2014)
In today’s high-velocity environment, organizations have to continually redefine their product offerings if they want to stay ahead in the competitive race. Lean budgets force organizations in particular the libraries who are cost-centres, to devise strategies that can manage change, leverage on knowledge and make the very most of the resources that are available. As globalisation facilitates collaboration, the techniques and tools of knowledge management (KM) contribute to information and knowledge sharing and delivery throughout the world. One way to do this was through cultivating communities of practice (CoPs), which are groups of people who share information, insight, experience, and tools about an area of common interest. Fostering these communities comprising of various strengths, skills and expertise to adapt the concepts of KM, knowledge workers were able to share their experiences, acquire new knowledge and know-how in enhancing operational efficacy and efficiency in delivering their library services. The paper seeks to explore the value created from implementing Kmaya (www.kmaya.com.my) an online community of practice that was designed to provide an informal learning platform for knowledge-seeking professionals in the library community in Malaysia.